CONSIDERAÇÕES ACERCA DA AUSÊNCIA PATERNA NA ADOLESCÊNCIA - Baccelli, Marcela Silva (2012)
The present study aimed to: a) Characterize a sample of adolescents participating in social projects of an Institution in the coast of Sao Paulo, b) Investigate the aspects of the structure and dynamics of adolescents from single parent families, conventional families and other family settings c) Understand the relationships established with parental figures for adolescents belonging to these different family organizations. To this end, initially a characterization of the profile of these adolescents was carried out and, subsequently, six cases of adolescents aged 12 to 18 years participating of Social Projects of the Third Sector (NGO) belonging to different forms of family organizations were studied. These teenagers were attended at the Institution where the data were collected. Semi -structured interviews and the Thematic Apperception Test were the instruments used. Overall, the results showed that adolescents from conventional families, that is, with father and mother within the family, were able to internalize the imago pattern in a more integrated way, and go through the adolescence in a more stable manner. The struggle to elaborate mourning is experienced, in tanden with the so-called "Normal Adolescence Syndrome". Youngsters representing families in which the father is not present, present defenses and anxieties characteristic of earlier stages of development. It is our conclusion that further studies are required to meet this demand, so that preventive work can create the conditions for good psychological development, enabling the passage through adolescence and achievement of adulthood in an integrated manner.